Hydrographic variability along the inner and mid-shelf region of the western Ross Sea obtained using instrumented seals. (May 2019) - Piñones, Andrea; Hofmann, Eileen E.; Costa, Daniel P.; Goetz, Kimberly; Burns, Jennifer M.; Roquet, Fabien; Dinniman, Michael S.; Klinck, John M.
Highlights: Ocean temperature and salinity were obtained from sensors deployed on Weddell seals. Erosion of the upper water column summer stratification is observed. Surface heat content accumulated during summer is eroded by synoptic wind events. Abstract: Temperature and salinity measurements obtained from sensors deployed on Weddell seals ( Leptonychotes weddellii ) between late austral summer and the following spring for 2010–2012 were used to describe the temporal and spatial variability of hydrographic conditions in the western Ross Sea, with particular emphasis on the inner-shelf region off Victoria Land and McMurdo Sound. Potential temperature-salinity diagrams constructed for regions where the seals remained for extended periods showed four water masses on the continental shelf: Modified Circumpolar Deep Water, Antarctic Surface Water, Shelf Water and Modified Shelf Water. Depth-time distributions of potential density and buoyancy frequency showed the erosion of the upper water column stratification associated with the transition from summer to fall/winter conditions. The within-year and interannual variability associated with this transition was related to wind speed. Changes in upper water column density were positively correlated with cross-shelf wind speeds >5.5 m s −1 with a 3–4 day lag. A range of wind speeds was required to erode the density structure because of different levels of stratification in each year. A comparison of wind mixing potential versus stratification (Wedderburn number) showed that synoptic scale wind events during 2012 with speeds of 5.5 and 6.5 m s −1 were needed to erode the summer stratification for Ross Island and Victoria Land regions, respectively. Stronger winds (>8.5 m s −1 ) were required during 2010 and 2011. The interannual variability in total heat content accumulated during summer (about 20%) was related to the duration of open water, with the largest heat content occurring in 2012, which was characterized by a summer sea ice minimum stronger than other years and relatively higher mCDW influence over the mid and outer-shelf regions. The heat content was lost after mid-April and reached a minimum in winter as a result of deep winter convection. The quantitative analysis of hydrographic variability of the inner-shelf region of the western Ross Sea obtained from the seal-derived measurements provides a baseline for assessing future changes.